Effect of chemical absorption on Jeffery Fluid Flow in saturated Porous Media with variable thermal conductivity - Disu, Akeem Babatunde; Omokhuale, Emmanuel; Salawu, Sulyman Olakunle (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
This study investigates the impact of species absorption of Jeffery fluid flow through a saturated permeable medium with variable thermal conductivity. The dimensional partial nonlinear derivative model controlling the chemical reacting fluid flow is transformed to invariant form. The resulting flow equations are computed numerically using an approximated finite implicit Crack-Nicolson. A chemical absorption of fluid reactant occurs in a boundless vertical device. Computations are performed for different parameters to examine their sensitivity under isothermal temperature conditions. The computed results are offered graphically for qualitative and quantitative insights into the flow behaviour. The obtained outcomes revealed that the fluid flow rate rises with an increasing values of the parameters and, and it damps with upsurge in the values of the parameters, and. The heat transfer field is reduced with enhancing values of the thermal source, viscous dissipation and time, but declines for a boosted value of the terms suction and Prandtl number. Also, the mass transfer field is higher when mass absorption and time are increased, and diminish with an elevate in the values of Schmidt number and chemical reactions.